2022
DOI: 10.3389/fgene.2022.956805
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a ceRNA-based lncRNA–mRNA network to identify functional lncRNAs in premature ovarian insufficiency

Abstract: Premature ovarian insufficiency, characterized by ovarian infertility and low fertility, has become a significant problem in developed countries due to its propensity for late delivery. It has been described that the vital role of lncRNA in the development and progression of POI. The aim of this work was to create a POI-based lncRNA–mRNA network (POILMN) to recognize key lncRNAs. Overall, differently expressed mRNAs (DEGs) and differently expressed lncRNAs (DELs) were achieved by using the AnnoProbe and limma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…To uncover prognostic genes in prostate cancer, we performed univariate COX analysis on DEGs using the tinyarray R package in the GSE46602 cohort. Least absolute shrinkage and selection operator (LASSO) regression analysis was conducted by glmnet R package 18 . Prognostic genes were screened and carried for construct a risk score model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To uncover prognostic genes in prostate cancer, we performed univariate COX analysis on DEGs using the tinyarray R package in the GSE46602 cohort. Least absolute shrinkage and selection operator (LASSO) regression analysis was conducted by glmnet R package 18 . Prognostic genes were screened and carried for construct a risk score model.…”
Section: Methodsmentioning
confidence: 99%
“…Least absolute shrinkage and selection operator (LASSO) regression analysis was conducted by glmnet R package. 18 Prognostic genes were screened and carried for construct a risk score model. The risk score was calculated as follows: risk score = Σ (βi  Expi) (β: coefficients, Exp: mRNA expression level).…”
Section: Lasso Regressionmentioning
confidence: 99%
“…After obtaining significantly positively correlated lncRNA‐mRNA pairs, we adopted a comprehensive computational approach to identify significant ceRNA candidates 31 . Several methods have been used to predict the ceRNA network, such as the hypergeometric test, which predicts the ceRNAs based on the number of common miRNAs binding to mRNA or lncRNA 32–34 . These studies considered only a single parameter.…”
Section: Methodsmentioning
confidence: 99%
“…31 Several methods have been used to predict the ceRNA network, such as the hypergeometric test, which predicts the ceRNAs based on the number of common miRNAs binding to mRNA or lncRNA. [32][33][34] These studies considered only a single parameter. We used several attributes, such as expression levels of F I G U R E 1 Workflow of the study to obtain long non-coding RNA (lncRNA)-associated competing endogenous RNAs (ceRNAs) possibly involved in temozolomide (TMZ) resistance and tumor recurrence.…”
Section: Cerna Propensity Score Calculationmentioning
confidence: 99%
“…Prior investigations have implicated lncRNAs in the pathogenesis of diverse conditions, including cancer [ 9 ], immune dysfunction [ 10 ] and embryogenesis [ 11 ]. Our previous research also identified aberrantly expressed lncRNAs in POI [ 12 ]. Consequently, we are intrigued by the exploration of lncRNAs’ roles in POI.…”
Section: Introductionmentioning
confidence: 99%